2019
DOI: 10.3390/molecules24132444
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Defoliation on Phenolic Concentrations, Antioxidant and Antibacterial Activity of Grape Skin Extracts of the Varieties Blaufränkisch and Merlot (Vitis vinifera L.)

Abstract: Vitis vinifera L. has been highlighted by its many positive effects on human health, including antibacterial, anti-inflammatory and antioxidant activity due to its rich phytochemical content. Removing six basal leaves has great potential to influence the production of phytochemicals. The purpose of this study was to determine the impact of different terms of defoliation on the antioxidant and antibacterial activity of grape skin extracts of the Blaufränkisch and Merlot varieties. The total phenolic concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Little thought is, however, given to its potential as a source of commercially valuable products [ 45 , 58 ]. The chemical composition of marc can be affected by environmental (climate, soil type) [ 25 , 29 , 59 ] and viticultural factors (fertilization, defoliation, grape variety, maturity, and harvest time) [ 59 , 60 ], as well as by grape processing techniques employed during winemaking [ 59 ]. Whereas red wine undergoes a fermentation process, the musts are removed before alcoholic fermentation in the other wine varieties.…”
Section: Wine By-products—chemical Composition and Bioactive Compoundsmentioning
confidence: 99%
“…Little thought is, however, given to its potential as a source of commercially valuable products [ 45 , 58 ]. The chemical composition of marc can be affected by environmental (climate, soil type) [ 25 , 29 , 59 ] and viticultural factors (fertilization, defoliation, grape variety, maturity, and harvest time) [ 59 , 60 ], as well as by grape processing techniques employed during winemaking [ 59 ]. Whereas red wine undergoes a fermentation process, the musts are removed before alcoholic fermentation in the other wine varieties.…”
Section: Wine By-products—chemical Composition and Bioactive Compoundsmentioning
confidence: 99%
“…Our results agree with the study by Radovanovic et al [ 29 ] in which early defoliation of vines resulted in a significant increase in total phenol concentration as well as in antioxidant activity compared to the control. Pavic et al [ 30 ] observed a similar trend in the grape skins of the Merlot variety following leaf removal just after blooming. It has been observed that the antioxidant capacity differs among phenols being expressed at different levels, making it difficult to differentiate the relative contribution of the various phenolics to the total antioxidant capacity of berries.…”
Section: Discussionmentioning
confidence: 70%
“…The mean at-harvest total phenolics content in Syrah grapes was similar to those found in the dark blue-colored wine grapes cvs. Blaufränkisch and Merlot grown in temperate climate (Pavić et al, 2019), suggesting the adaptability of V. vinifera to maintain adequate levels of these relevant compounds even under suboptimal climate conditions. The preharvest application of elicitors to increase the content of phenolic compounds in grapes has shown contrasting results related to the species, cultivar, type of elicitor, and vintage (Sandhu et al, 2011;Ruiz-García et al, 2013;Gómez-Plaza et al, 2017).…”
Section: Figurementioning
confidence: 99%